Critical weed period in aerobic rice and weed control using chemicals - Arul Sebastian Micheal, Jaya Suria (2012)
Aerobic rice system is the most promising irrigation water saving technology, but is highly impeded by severe weed pressure. Weed control using same herbicide causes development of herbicide resistant weed biotypes and posing serious problem in weed management. This study was conducted to determine the most efficient selective rice herbicides under aerobic culture system while also considering the economics of the chemical weed control method through determination of critical period for weed control (CPWC). Two CPWC experiments were conducted from November 2007 to March 2008 at the Malaysian Agricultural Research and Development Institute, Seberang Perai, Penang, Malaysia. The study was realized by investigating the durations of weed interference and weed-free period which respectively determines beginning and end of CPWC. Results showed that by using a local aromatic rice variety, MRQ74 in aerobic rice cultivation, its rice yield would be severely impaired if weeds were not removed from 17 to 53 days after sowing (DAS). An acceptable yield loss at 5% could be gained if weeds were controlled from 11 DAS until harvest at 74 DAS. Meanwhile, CPWC study on an aerobic rice nursery line, AERON001 had significant competitions from 13 to 75 DAS for a 5% acceptable yield loss, and from 29 to 40 DAS for a 10% acceptable yield loss. The screenings of selective rice herbicides were conducted during off season (April –July 2008) and main season (November 2008 – February 2009) to evaluate fourteen and eight herbicide treatments, respectively. Weed free control and weedy check treatments were also included in both trials. The trial used a randomized complete block design with three replications in the off season, and four replications in the main season. Twenty five weed species were found in the aerobic rice field but two species (Eleusine indica and Digitaria ascendens) seemed to be dominant. Based on the weed control efficiency, weed index values, and net benefit economic analysis, it was shown that the herbicide combinations of Propanil/Thiobencarb (1.2 kg ai ha- 1/2.4 kg ai ha-1) followed by Bentazone/MCPA (0.6 kg ai ha-1/0.1 kg ai ha-1) or Cyhalofop-butyl + Bensulfuron (0.1 kg ai ha-1 + 0.06 kg ai ha-1) followed by Bentazone/MCPA (0.6 kg ai ha-1/0.1 kg ai ha-1) or Pendimethalin (1.0 kg ai ha-1) followed by Cyhalofop-butyl + Bensulfuron (0.1 kg ai ha-1 + 0.06 kg ai ha-1) followed by Bentazone/MCPA (0.6 kg ai ha-1/0.1 kg ai ha-1) or Pretilachlor + Pendimethalin (0.375 kg ai ha-1/0.75 kg ai ha-1) followed by Bentazone/MCPA (0.6 kg ai ha-1/0.1 kg ai ha-1) could be the possible alternative for effective and economic weed control in rice under aerobic system. Based on these results and CPWC, the abovementioned selective rice herbicides should be applied at or before 11 DAS followed by sequential application by latest 43 DAS to maximize aerobic rice yield and minimize weed biomass.